Верификация программ: состояние, проблемы, результаты. I - Крывый, С.Л.; Максимец, А.Н. (Кибернетика и системный анализ, 2013)
Представлено аналiтичний огляд сучасних методiв верифiкацiї програмного забезпечення послiдовних, функцiональних, паралельних та розподiлених систем. Основну увагу придiлено методам верифiкацiї на основi властивостей абстрактних iнтерпретацiй, транзицiйних систем, мереж Петрi. An analytical survey of the modern verification methods for sequential functional, reactive, and distributed systems is presented. The main attention is given to the methods that are based on the properties of abstract interpretation, transition systems, and Petri nets.